MASA KRISIS PERKEBUNAN TEBU DAN INDUSTRI GULA DI WILAYAH GERBANG KERTASUSILA PASKA PEMERINTAHAN SOEHARTO (1998-SEKARANG) - Artono; Widodo, Hananto; Nugroho, Arinto (Universitas Negeri Surabaya, 2024)
East Java was originally a sugarcane plantation and the main sugar producer in Indonesia. This inability is caused by the decreasing land for planting sugarcane, especially in Java. Since the 19th century, the islands of Java and Sumatra have been among the largest sugar producers. The largest land area is on the island of Java. The quality of the soil and climate are very good for sugar plants. The problem is land conversion. Land conversion occurs due to the development of large cities and their satellite cities. The development of these cities requires land for residential and factory functions. This is actually not a problem as long as there is careful planning and strict implementation of the spatial planning of the area. This study tries to examine the synergy between sugarcane plantations and spatial planning and its implementation. By examining the case of the closure of three sugar factories in Sidoarjo Regency, the study shows that inconsistency in maintaining planting land has resulted in sugar factories experiencing difficulties in sugarcane supply.